3D-MDCT study of styloid process of temporal bone among patients at-tending Chitwan Medical College Teaching Hospital - Khan, Gulam Anwer; Khatiwada, Sushma; Shakya, Shuvechha; Adhikari, Deepak; Gautam, Ajeevan (Journal of Chitwan Medical College, 2021)
Background: The styloid process of the temporal bone is clinically significant because differences in length and angulations are linked to the symptoms of stylalgia (Eagle’s syndrome), and surgical removal of the process can help patients with neck and cervico-facial pain. This study aimed to evaluate the length, angulation and distance between bases and tips of the styloid process. Methods: A Hospital based cross-sectional study using observation method was carried out in Department of radiology Chitwan Medical College Teaching Hospital, Nepal from 17th September 2021 to 16th November 2021. A total of 107 patients were enrolled as a sample for the study. The length, distance and angulation were measured during routine 3D Multi-detector row computed tomography (MDCT). Obtained data was evaluated by using descriptive statistics with Statistical Package for the social Science (IBM SPSS) 20.0. Results: Among 107 patients undergoing Computed Tomography (CT) scan, majority i.e 71% have medial angulation of styloid process, 16.80% participants have elongated styloid process on left side and 17.80 % participants have elongated styloid process on right side. Mann Whitney U Test showed that tip to tip and base to base distance are statistically significant between male and female. Conclusions: The styloid process is in close proximity to a number of essential anatomical structures. Because of differences in the shape of the styloid process, these structures may be compressed or inflamed. Even though the existence of an elongated styloid process and its angulation is uncommon, it emphasizes the need of examining the styloid process on a regular basis in clinical practice.